Exploring the need of knowledge management education within library and information science educational courses: An Indian perspective. Issue 11 (9th November 2015) - Husain, Shabahat; Nazim, Mohammad
Abstract : Purpose: – The study aims to explore the relevance of knowledge management (KM) education within library and information science (LIS) educational courses in India. Design/methodology/approach: – The study used a quantitative research approach. A Web-based questionnaire survey was designed and distributed throughFreeOnlineSurveys.com for the collection of data. A link for attending the survey was sent via electronic mail to the teachers (95 in numbers) of 65 LIS schools. A total of 43 responses (approximately 45 per cent) were received. Findings: – The findings show that there is a strong interest among LIS community towards the inclusion of KM education within LIS educational courses to impart the knowledge and skills related to KM among LIS students, and to facilitate their entry into the KM job market. Most of the respondents believe that a curriculum which embodies core elements of LIS, management and information systems and technology would best meet the needs of LIS students for their involvement in KM activities. Practical implications: – Findings of the present study may be used as the groundwork for the revision of current LIS educational courses as well as the revision of LIS curricula to impart the knowledge and skills-related to KM among LIS students for working in KM environment. Originality/value: – As no empirical study on the relevance of KM education to LIS professionals in India has been carried out before, this study closes this gap and provides a framework to modify existing LIS courses or curricula to fulfil the requirement of KM competencies of LIS students.